تحليل تطبيق طريقة الثواب والعقاب لتنفيذ بيئة اللغوية لطلاب الصف الثامن المتوسط بمعهد المسلمون العصري لهوك سكون أتشيه الشمالية - Pujiati, Pujiati; Ramadona, Syahri; Marzian, Rozzatul (Lembaga Yasin AlSys, 2024)
The formulation of the problem in this research is 1) how to apply reward and punishment methods to run a language environment for class VIII students at MTs Pondok Pesantren Terpadu Al-Muslimun? 2) What causes class VIII students at MTs Podok Pesantren Terpadu Al-Muslimun to receive rewards and punishments? The aims of this research are 1) to find out how to apply the reward and punishment method to run a language environment for class VIII students at MTs Pondok Pesantren Terpadu Al-Muslimun, 2) to find out the reasons why students in class VIII MTs Podok Pesantren Terpadu Al-Muslimun get rewards and punishments. This research is qualitative research using descriptive methods, data collection methods using interviews, observation and documentation, as well as data analysis methods using the Miles and Humen methods.